PENINGGALAN SEJARAH KRATON SURAKARTA SEBAGAI MEDIA PEMBELAJARAN SEJARAH KELAS IV DAN V SD NEGERI DI KECAMATAN BANJARSARI DAN JEBRES - Mukhlis Mustofa, Sarafuddin & (UNIVERSITAS SLAMET RIYADI, 2015)
This research aims at describing (1) the reasons why the teachers of elementary school atpublic schools do not use the heritage of Keraton Kasunanan Surakarta as a learning media incharacter building; (2) the learning media in character building used by the teachers ofelementary school at public schools in Surakarta in achieveing the given competence and thelearning goal; (3) the heritage of Keraton Kasunanan Surakarta which may be used as as alearning media in character building in public elementari schools in Surakarta; (4) the ways howthe heritage of Keraton Kasunanan Surakarta used as a learning media in character buildingeffectively.The result of the research conclude that (1) the reasons why the teachers of elementaryschool at public schools do not use the heritage of Keraton Kasunanan Surakarta as a learningmedia in character building are about the cost (2) the learning media in character building usedby the teachers of public elementari school are those related to history subjet fo grade IV and V;(3) the heritage of Keraton Kasunanan Surakarta used as as a learning media in characterbuilding in public elementari schools in Surakarta should be packaged in CD for learning withgood quality voice in the explanation. For this purpose, the teachers’ advice is needed.Keywords; the heritage of Keraton Kasunanan Surakarta, learning media, character building.